Timing analysis of two-electron photoemission - Kheifets, A.; Ivanov, I.; Bray, Igor (Institute of Physics Publishing Ltd., 2011)
We predict a significant delay of two-electron photoemission from the helium atom after absorption of an attosecond XUV pulse. We establish this delay by solving the time-dependent Schr¨odinger equation and by subsequently tracing the field-free evolution of the two-electron wave packet. This delay can also be related to the energy derivative of the phase of the complex double-photoionization (DPI) amplitude which we evaluate by using the convergent close-coupling method. Our observations indicate that future attosecond time delay measurements on DPI of He can provide information on the absolute quantum phase and elucidate various mechanisms of this strongly correlated ionization process.